SAT-637 Patient-Centered Glycemic Management of Type 2 Diabetes with Mobile Applications - Lau, Chap-Kay K (J Endocr Soc, 2020)
BACKGROUND: Ehealth apps have 3.7 billion downloads yearly. The accessibility of diabetes mobile applications allows for patient self-management of diabetes. Renal and cardiovascular complications,(1) which play a role in diabetic patient outcomes, are newly highlighted by the 2019 American Diabetes Association’s Standards of Medical Care in Diabetes.(2) Purpose: To evaluate free Android mobile apps using the Diabetes Self-Management Education and Support (DSMES) and the 2019 American Diabetes Association (ADA) guidelines for renal and cardiovascular complications. Methods: Using the search term “diabetes,” Google Play store was accessed. Inclusion criteria: 1) Apps with downloads 1M-100,000; 2) free; 3) DSMES criteria; and 4) medication adherence. Exclusion criteria: 1) Purely educational factual apps on diabetes; 2) no ranking or download information. Google displayed a list of 10 free apps in 2019. The 2019 apps were analyzed for DSMES criteria, renal and cardiovascular complications (ADA 2019), and medication adherence via push notification. Results: The top 10 mobile apps in descending order were: 1) mySugr, 2) Onetouch Reveal, 3) OneDrop Diabetes Management, 4) Diabetes: M, 5) Diabetes, 6) Ontrack Diabetes, 7) Health2Sync, 8) Diabetes Connect, 9) Glucose Buddy Diabetes Tracker, 10) Blood Glucose Tracker. All of the mobile apps had the functionality of tracking blood glucose levels. 8/10 had the ability of tracking HbA1C levels. The percent of DSMES incorporation within the apps ranged from 18.2%-81.8%. None of the apps used all the DSMES guidelines or 2019 ADA. Only 1/10 of the mobile apps had the ability to track the presence of heart palpitation and retina/eye issues recommendations. None of the apps had the ability to track cardiovascular and renal complications. 7/10 of the apps had medication reminders (sound notification) and 4/10 of the apps had push notifications. Conclusion: eHealth mobile apps could be a powerful tool for patient self-management of diabetes. Currently, none of the apps incorporate all of the DSMES or ADA guidelines regarding comorbidities and complications of diabetes. Despite these shortcomings, these apps provide an introduction to the concept of patient-centered tracking of health data. We look for future improvements as more physicians use the apps and provide feedback to the app developers and eHealth commerce space. References 1. Davies MJ, D’Alessio DA, Fradkin J, et al. Management of hyperglycemia in type 2 diabetes, 2018. A consensus report by the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD). Diabetes Care 2018;41:2669-2701 2. American Diabetes Association. 4. Comprehensive medical evaluation and assessment of comorbidities: Standards of Medical Care in Diabetes—2019. Diabetes Care 2019;42(Suppl. 1):S34-S45